2017
DOI: 10.1200/jgo.2016.004614
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Survival With Mastectomy Vis-à-Vis Breast-Conserving Surgery in Stage II and III Breast Cancers: A Comparative Treatment Effectiveness Study

Abstract: PurposeThe primary purpose of hospital-based cancer registries is assessing patient care. Clinical stage–based survival and treatment-based survival are some of the key parameters for such assessment. Because of the challenges in obtaining follow-up parameters, a separate study on patterns of care and survival was undertaken by the Indian National Cancer Registry Program. The results for cancer of the female breast are presented here.Patients and MethodsData abstracted in a standardized patient information for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…As per the ICMR data based on cumulative analysis of data from 13 institutions across the country, the cumulative 5-year survival of a cohort of 7609 patients was 73.8%. [ 10 ] Subsequently, there have been a few more studies which have looked at 5-year OS,[ 9 ] which showed better survival, but no Indian data looked at 10-year survival outcome and more. Globally, also there have been only a small number of studies looking at more than 10-year survival outcome from a single hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As per the ICMR data based on cumulative analysis of data from 13 institutions across the country, the cumulative 5-year survival of a cohort of 7609 patients was 73.8%. [ 10 ] Subsequently, there have been a few more studies which have looked at 5-year OS,[ 9 ] which showed better survival, but no Indian data looked at 10-year survival outcome and more. Globally, also there have been only a small number of studies looking at more than 10-year survival outcome from a single hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Available data from India are mainly on 5-year survival figures from some of the major cancer treatment centers. [ 8 9 10 ] Many patients are lost to follow-up after 5 years of primary treatment at oncology centers, even after the importance of follow-up visit is explained. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…In all of these trials, not only was there no inferiority for BCS versus mastectomy regarding local recurrences, distant metastases, and overall survival but also many studies showed benefits for breast conservation therapy (BCT) over mastectomy. Besides, some trials demonstrated a slightly more favorable outcome in patients with positive nodes treated with BCS; however, the differences were not statistically significant [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple prospective randomized trials [4], some with a follow-up of 20 years, have established equivalent survival rates between mastectomy and breast conservation surgery (BCS) with negative margins. Recent studies from various countries including India indicate that women treated with BCT have a significant survival advantage when compared to mastectomy [57].…”
Section: Introductionmentioning
confidence: 99%